Challenges of the private health plans regulation in Brazil - Carlos Octávio Ocké-Reis (Institute for Applied Economic Research (ipea), 2015)
The idea of regulating private health plans so as to favor major players and the "managed care" is incompatible with the guidelines of the National Health System [Sistema Único de Saúde (SUS)] and for this reason we defend instead a regulatory action aiming to strengthen the public sphere. In particular, we discuss how this alternative could improve the regulatory capacity of the National Supplementary Health Agency [Agência Nacional de Saúde Suplementar (ANS)] to face the economic crisis in the health plan marketplace, dispelling the mistaken notion that the market, once strengthened, will cooperate with the SUS rather than contaminate it.
Keywords: 330